Functional changes in the media system of the late twentieth and early twenty-first century (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with the media system and outlines functional changes in media discourse of the late twentieth and early twenty-first centuries caused by linguistic and nonlinguistic reasons. The paper also shows functional shifts and fixes general enlargement of functions within media discourse.
Keywords: media; media discourse; function